ChatGPT For Marketing Communications: Friend or Foe? - Heidy Arviani; Ririn Puspita Tutiasri; Latif Ahmad Fauzan; Ade Kusuma (Kanal: Jurnal Ilmu Komunikasi, 2023)
The release of the ChatGPT chatbot in November 2022 received significant public attention. ChatGPT is an Artificial Intelligence (AI) powered chatbot that allows users to simulate human-like conversations with AI. GPT stands for Generative Pre-trained Transformer, a language processing model developed by the American artificial intelligence company OpenAI. These innovations and technologies are changing business interests, revolutionizing marketing communications strategies, and enhancing the consumer experience. ChatGPT is a powerful tool for marketers, but we need to understand the risks and place realistic expectations for the moment. The author uses data collection techniques using literature studies and observations on ChatGPT about their potential and impact on marketing communications. Authors analyze brand information, data search, reference services, cataloging, content creation, and ethical considerations such as privacy and bias. Result of this study, ChatGPT can provide and support creative content creation or copywriting, improve customer service, automate repetitive tasks, and support data analysis. However, humans are irreplaceable for examining outputs and creating marketing messages consistent with a company's strategy and brand vision. With good marketing strategies, ChatGPT can effectively enhance and support marketing processes.